Changes in Handwriting due to Alzheimer’s Disease a Case Report - Birincioğlu, İsmail and Uzun, Mustafa and Alkan, Nevzat and Kurtaş, Ömer and Yılmaz, Rıza and Can, Muhammet (The Bulletin of Legal Medicine, 2016)
Handwriting and signature comparisons are frequently performed in forensic investigations of documents. Mistakes in conclusion might be due to lack of sufficient documentation and information. Many factors can affect handwriting and signature. These factors are divided into two groups: dependent or independent of the individual at the time the handwriting or signature is made. Therefore, the situations leading to differences between individuals and in the individual’s own handwriting and signature should be determined. Currently, average life expectancy and quality have increased due to the developments in health services. Thus, an increasing number of elderly people are engaged in an active daily life and trade. Alzheimer’s Disease (AD) can develop in the elderly; this is a condition that could alter handwriting and signature considerably over time. In forensic document examination, comparing the document in question containing handwriting or signature with the original documents prepared before the document in question was prepared is important. However, if alterations have developed secondary to a disease, the documents prepared before and after the disease affected the individual should be assessed together. Likewise, in the present case, the examiners making comparisons using handwriting and signatures from different periods reached entirely different conclusions. The case is a bill prepared in 1994. The payee of the bill is a male born in 1925 and diagnosed with AD shortly before his death in 1998. The indebted person in the bill is the payee’s spouse. For the assessment of handwriting and signature, the first endorsement consisting of the handwritten name and signature was used. Several expert reports regarding the same document had been commissioned; these reached different views. The document was sent to The Council of Forensic Medicine to assess the identification and the previous reports. After re-evaluation, the handwriting was declared to belong to the payee. In this study, the reason that the experts delivered opposing opinions on the identification of a document handwritten by a person with AD after being referred to court was investigated. Based on the judicial file, the document examiners did not have the opportunity to evaluate all factors affecting the handwriting or signature of the individual, and an adequate number of handwriting and signature examples were not collected for comparison. Consequently, the examiners reached differing opinions. Thus, the above-mentioned factors are necessary to derive a satisfactory and accurate opinion regarding the identification of handwriting or signature. Keywords: Forensic sciences, handwriting, signature, Alzheimer’s Disease.